Is Tribology Approaching Its Golden Age? Grand Challenges in Engineering Education and Tribological Research - Popov, Valentin L. (Frontiers in Mechanical Engineering, 2018)
In spite of its obvious importance, the subject of tribology has relatively low visibility in the engineering community and among the general public. The author's hypothesis is that this problem is at least partly due to the poor “availability” of tribology. In other words, there are practically no simple methods or concepts having high predictive power for tribological problem-solving. That situation is due to the extremely inter-disciplinary and multi- scale character of tribological processes. Fortunately, however, recent methodical and didactical developments in the field of tribology offer hope that the situation may soon change. It is time to integrate certain basic aspects of the mechanics of interfaces into the curricula of technical universities. The author further argues that one of the key problems confronting tribology and its future grand challenges is solving the problem of the “third body.”